1991
DOI: 10.1159/000186278
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Elevation during the Night in Chronic Renal Failure, Hemodialysis and after Renal Transplantation

Abstract: Diurnal blood pressure variation was studied by ambulatory 24-hour monitoring in patients with advanced chronic renal failure (n = 20), on chronic hemodialysis (n = 20), after renal transplantation (n = 21) and in matched control groups without renal disease. Nocturnal blood pressure reductions were significantly blunted in all patient groups as compared with the respective control groups. In almost none of the 61 controls did the mean values during nighttime (8 p.m.-8 a.m.) exceed the mean day time values (8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
49
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(60 citation statements)
references
References 18 publications
9
49
0
1
Order By: Relevance
“…[47][48][49][50][51][52] Because the degree of non-dipping was closely correlated with the degree of renal function loss, as discussed above, 38,40 however, non-dipping might be consequently correlated with the progression of nephropathy. Our clear results especially obtained after kidney donation 40 that instead it might be a phenotype of renal functional loss, together with well known facts that in patients with renal dysfunction the nocturnal BP dip is lost and circadian rhythms manifest as those of non-dippers, 38,40,47,50,53,54 suggest that the circadian rhythm of BP is determined mostly by the kidneys. The importance of kidneys in the genesis of circadian BP rhythm is consistent with reports that the circadian rhythm of BP is normalized from non-dipper to dipper after kidney transplantation, 55 and also by salt intake restriction and diuretics.…”
Section: Salt Sensitivity and Circadian Rhythm Of Blood Pressuresupporting
confidence: 53%
“…[47][48][49][50][51][52] Because the degree of non-dipping was closely correlated with the degree of renal function loss, as discussed above, 38,40 however, non-dipping might be consequently correlated with the progression of nephropathy. Our clear results especially obtained after kidney donation 40 that instead it might be a phenotype of renal functional loss, together with well known facts that in patients with renal dysfunction the nocturnal BP dip is lost and circadian rhythms manifest as those of non-dippers, 38,40,47,50,53,54 suggest that the circadian rhythm of BP is determined mostly by the kidneys. The importance of kidneys in the genesis of circadian BP rhythm is consistent with reports that the circadian rhythm of BP is normalized from non-dipper to dipper after kidney transplantation, 55 and also by salt intake restriction and diuretics.…”
Section: Salt Sensitivity and Circadian Rhythm Of Blood Pressuresupporting
confidence: 53%
“…Fromthese results, sympathetic activity was found to be a contributor to hypertension in chronic renal insufficiency as Ligtenberg et al recently confirmed (34). Similar findings were also reported by Baumgart et al (32), who demonstrated significantly lower differences in blood pressure between the awake and sleeping time in patients with chronic renal insufficiency compared to control subjects. From these studies, it is suggested that somesubjects with predialysis renal disease may have hidden hypertension at night.…”
Section: Aggressive Blood Pressure Reduction In Patients With Chronicsupporting
confidence: 82%
“…This phenomenonis usually recognized as morning surge of blood pressure. Accumulative evidence clearly demonstrate that ambulatory blood pressure levels, compared with office blood pressure levels, are moreclosely related to hypertensive organ damage (27)(28)(29)(30)(31)(32). Portaluppi et al (29) monitored blood pressure in 30 hospitalized hypertensive patients (mean age, 45 years) who were not undergoing dialysis but had advanced renal disease (mean creatinine clearance, 25 ml/min) and in 30 matched essential hypertensive patients with normal renal function (creatinine clearance 1 14 ml/min).…”
Section: Aggressive Blood Pressure Reduction In Patients With Chronicmentioning
confidence: 99%
“…Indeed, in renal disease, nondipping is the rule, with a prevalence between 74% and 82%. [25][26][27][28][29] Crosssectional observations have demonstrated that nondippers have more severe morphological 30 and functional 31,32 changes than dippers. Fukuda et al 31 studied subjects with biopsy-proven glomerulopathy and found that creatinine clearance (Cl Cr ) was significantly negatively related to the night/day ratios of both sodium excretion and MAP, whereas Farmer et al 32 have shown that the prevalence of nondipping increases with plasma creatinine concentration in patients with chronic renal insufficiency.…”
Section: Nocturnal Blood Pressure Dipping and Sodium Excretionmentioning
confidence: 99%